Understanding the circumstances and stakeholder perceptions of gun violence restraining order use in California: a qualitative study - Pallin, Rocco (Criminology & public policy, 2021)
Risk-based firearm removal policies are relatively new, and research on their implementation and effectiveness is limited. Using an interpretive phenomenological approach, we interviewed stakeholders in California's gun violence restraining order (GVRO) process to learn about circumstances in which GVROs are appropriate. Two primary themes emerged: (1) GVROs are most useful when there is acute risk of harm with a firearm, in the context of cognitive decline, or as related cases proceed through the courts, and (2) GVROs fill a gap in the policy landscape. Perceptions varied regarding the role of GVROs among preexisting violence prevention tools. Several informants perceived racial/ethnic disparities in GVRO use.